Are Some Countries More Prone to Pressure Evaluators Than Others? Comparing Findings From the United States, United Kingdom, Germany, and Switzerland. (September 2017) - Pleger, Lyn; Sager, Fritz; Morris, Michael; Meyer, Wolfgang; Stockmann, Reinhard
Pressure on evaluators has been investigated recently by surveys in the USA, the UK, Germany, and Switzerland. This study compares the results of those studies regarding pressure on evaluators in different countries. The findings suggest that independence of evaluations does not exist for many respondents. Moreover, the person who commissioned the evaluator for evaluation is identified by all studies as the primary influencing stakeholder in the evaluation process. In terms of differences, Germany seems to be more prone to pressure on evaluators. However, German evaluators do not show stronger tendencies to surrender to pressure than the other countries' respondents. We suggest that this pattern may be explained by the strong state tradition in Germany as opposed to the U.S. and Switzerland, in conjunction with evaluators' profession-based, principled resistance to such pressure.